Svarthamaren seabirds, sentinels of the Southern Ocean - Descamps, Sébastien; Moreau, Sébastien; Tarroux, Arnaud; Lorensten, Svein-Håkon; Bustnes, Jan-Ove; Yoccoz, Nigel G; Borgå, Katrine; Carravieri, Alice; Patrick, Samantha (Fram forum, 2021)
Keywords: Sørishavet; forurensning; klimaendringer; marin biologi; marine økosystemer; miljøendringer; observasjoner; ornitologi; sjøfugler; zoologi; økologi

An ocean of possibilities: antarctic petrel's foraging in the Southern Ocean - Tarroux, Arnaud; Fauchald, Per; Varpe, Øystein; Yoccoz, Nigel G; Descamps, Sébastien (Fram forum, 2021)
Keywords: Sørishavet; fôring; marin biologi; observasjoner; ornitologi; petreller; sjøfugler; zoologi

High inter- and intraspecific niche overlap among three sympatrically breeding, closely related seabird species: Generalist foraging as an adaptation to a highly variable environment? - Dehnhard, Nina; Achurch, Helen; Clarke, Judy; Michel, Loïc N; Southwell, Colin; Sumner, Michael D; Eens, Marcel; Emmerson, Louise (Journal of Animal Ecology, 2020)
Ecological niche theory predicts sympatric species to show segregation in their spatio-temporal habitat utilization or diet as a strategy to avoid competition. Similarly, within species individuals may specialize on specific dietary resources or foraging habitats. Such individual specialization seems to occur particularly in environments with predictable resource distribution and limited environmental variability. Still, little is known about how seasonal environmental variability affects segregation of resources within species and between closely related sympatric species. The aim of the study was to investigate the foraging behaviour of three closely related and sympatrically breeding fulmarine petrels (Antarctic petrels Thalassoica antarctica, cape petrels Daption capense and southern fulmars Fulmarus glacialoides) in a seasonally highly variable environment (Prydz Bay, Antarctica) with the aim of assessing inter- and intraspecific overlap in utilized habitat, timing of foraging and diet and to identify foraging habitat preferences. We used GPS loggers with wet/dry sensors to assess spatial habitat utilization over the entire breeding season. Trophic overlap was investigated using stable isotope analysis based on blood, feathers and egg membranes. Foraging locations were identified using wet/dry data recorded by the GPS loggers and expectation-maximization binary clustering. Foraging habitat preferences were modelled using generalized additive models and model cross-validation. During incubation and chick-rearing, the utilization distribution of all three species overlapped significantly and species also overlapped in the timing of foraging during the day—partly during incubation and completely during chick-rearing. Isotopic centroids showed no significant segregation between at least two species for feathers and egg membranes, and among all species during incubation (reflected by blood). Within species, there was no individual specialization in foraging sites or environmental space. Furthermore, no single environmental covariate predicted foraging activity along trip trajectories. Instead, best-explanatory environmental covariates varied within and between individuals even across short temporal scales, reflecting a highly generalist behaviour of birds. Our results may be explained by optimal foraging theory. In the highly productive but spatio-temporally variable Antarctic environment, being a generalist may be key to finding mobile prey—even though this increases the potential for competition within and among sympatric species.
Keywords: Antarktis; biologging; klimaendringer; observasjoner; ornitologi; overvåking; sjøfugler; stabile isotoper; zoologi; økologi; økosystemer

Post-depositional loss of nitrate and chloride in Antarctic snow by photolysis and sublimation: a field investigation - Noro, Kazushi; Takenaka, Norimichi (Polar Research, 2020)
Nitrate in snow is subject to post-depositional processing, which leads to a net loss and redistribution within the snowpack. The relative importance of post-depositional loss processes such as the volatilization of nitric acid (HNO3) and photolysis of nitrate has long been debated. Changes in nitrate and chloride concentrations in the snowpack were investigated at H128 (69°23.584’S, 41°33.712’E), an Antarctic coastal site approximately 100 km from Syowa Station in East Antarctica from December 2015 to February 2016. Results indicate that chloride migrated to deeper sites within the snowpack under the influence of water vapour movement. Moreover, 50% of the nitrate on surface snow was lost to photolysis, and approximately 20% of the nitrate was absent at a depth of 40 cm. To enhance our knowledge of the Antarctic geochemical cycle, this study is the first to suggest chloride ion movement in snowpacks or significant nitrate loss for any Antarctic coastal site.
Keywords: Antarktis; geokjemi; kromatografi; observasjoner; ozon; snø; temperatur

Foraging tactics in dynamic sea-ice habitats affect individual state in a long-ranging seabird - Tarroux, Arnaud; Cherel, Yves; Fauchald, Per; Kato, Akiko; Love, Oliver P; Ropert-Coudert, Yan; Spreen, Gunnar; Varpe, Øystein; Weimerskirch, Henri; Yoccoz, Nigel G; Zahn, Sandrine; Descamps, Sébastien (Functional Ecology, 2020)
Abstract Individual heterogeneity in diet and foraging behaviour is common in wild animal populations, and can be a strong determinant of how populations respond to environmental changes. Within populations, variation in foraging behaviour and the occurrence of individual tactics in relation to resources distribution can help explain differences in individual fitness, and ultimately identify important factors affecting population dynamics. We examined how foraging behaviour and habitat during the breeding period related to the physiological state of a long-ranging seabird adapted to sea ice, the Antarctic petrel Thalassoica antarctica. Firstly, using GPS tracking and state-switching movement modelling (hidden Markov models) on 124 individual birds, we tested for the occurrence of distinct foraging tactics within our study population. Our results highlight a large variation in the movement and foraging behaviour of a very mobile seabird, and delineate distinct foraging tactics along a gradient from foraging in dense pack ice to foraging in open water. Secondly, we investigated the effects of these foraging tactics on individual state at return from a foraging trip. We combined movement data with morphometric and physiological measurements of a suite of plasma metabolites that provided a general picture of a bird's individual state. Foraging in denser sea ice was associated with lower gain in body mass during brooding, as well as lower level of energy acquisition (plasma triacylglycerol) during both brooding and incubation. We found no clear relationship between the foraging tactic in relation to sea ice and the energetic stress (changes in plasma corticosterone), energetic balance (β-hydroxybutyrate) or trophic level (δ15N). However, a shorter foraging range was related to both the energetic balance (positively) and the trophic level (negatively). Our results highlight a diverse range of foraging tactics in relation to sea ice in Antarctic petrels. While the various foraging tactics do not seem to strongly alter energetic balance, they may affect other aspects of Antarctic petrels' physiology. Future changes in sea-ice habitats can thus be expected to have an impact on the individual state of seabirds such as Antarctic petrels, which could ultimately affect their population dynamics. Nonetheless, strong individual heterogeneity in the use of sea-ice habitats by a typical pagophilic species might strengthen its resilience to environmental changes and in particular to forecasted sea-ice loss. A free Plain Language Summary can be found within the Supporting Information of this article.
Keywords: Sørishavet; fôring; havis; marin biologi; miljøendringer; observasjoner; ornitologi; petreller; sjøfugler; sjøis; smelting; zoologi

Warm Circumpolar Deep Water at the Western Getz Ice Shelf Front, Antarctica - Assmann, Karen; Darelius, Elin Maria K; Wåhlin, Anna K; Kim, Tae Wan; Lee, Sang Hoon (Geophysical Research Letters, 2019)
The Getz Ice Shelf is one of the largest sources of fresh water from ice shelf basal melt in Antarctica. We present new observations from three moorings west of Siple Island 2016–2018. All moorings show a persistent flow of modified Circumpolar Deep Water toward the western Getz Ice Shelf. Unmodified Circumpolar Deep Water with temperatures up to 1.5 °C reaches the ice shelf front in frequent episodes. These represent the warmest water observed at any ice shelf front in the Amundsen Sea. Mean currents within the warm bottom layer of 18–20 cm/s imply an advection time scale of 7 days from shelf break to ice shelf front. Zonal wind stress at the shelf break affects heat content at the ice shelf front on weekly to monthly time scales. Our 2-year mooring records also evince that upwelling over the shelf break controls thermocline depth on subannual to annual time scales.
Keywords: Antarktis; geofysikk; glasiologi; isbrem; isshelf; observasjoner

Assessment of Atmospheric Reanalyses With Independent Observations in the Weddell Sea, the Antarctic - Jonassen, Marius O; Välisuo, Ilona; Vihma, Timo; Uotila, Petteri; Makshtas, Alexander P; Launiainen, Jouko (Journal of Geophysical Research: Atmospheres, 2019)
Surface layer and upper-air in situ observations from two research vessel cruises and an ice station in the Weddell Sea from 1992 and 1996 are used to validate four current atmospheric reanalysis products: ERA-Interim, CFSR, JRA-55, and MERRA-2. Three of the observation data sets were not available for assimilation, providing a rare opportunity to validate the reanalyses in the otherwise datasparse region of the Antarctic against independent data. All four reanalyses produce 2 m temperatures warmer than the observations, and the biases vary from +2.0 K in CFSR to +2.8 K in MERRA-2. All four reanalyses are generally too warm also higher up in the atmospheric boundary layer (ABL), with biases up to +1.4 K (ERA-Interim). Cloud fractions are relatively poorly reproduced by the reanalyses, MERRA-2 and JRA-55 having the strongest positive and negative biases of about +30 % and −17 %, respectively. Skill scores of the error statistics reveal that ERA-Interim compares generally the most favorably against both the surface layer and the upper-air observations. CFSR compares the second best and JRA-55 and MERRA-2 have the least favorable scores. The ABL warm bias is consistent with previous evaluation studies in high latitudes, where more recent observations have been applied. As the amount of observations has varied depending on the decade, season, and region, the consistency of the warm bias suggests a need to improve the modeling systems, including data assimilation as well as ABL and surface parameterizations.
Keywords: Sørishavet; Weddellhavet; atmosfæren; geofysikk; meteorologi; observasjoner

Distribution, density and abundance of Antarctic ice seals off Queen Maud Land and the eastern Weddell Sea - Gurarie, Eliezer; Bengtson, John L; Bester, Marthán N; Blix, Arnoldus Schytte; Cameron, Michael; Bornemann, Horst; Nordøy, Erling S; Plötz, Joachim; Steinhage, Daniel; Boveng, Peter (Polar Biology, 2017)
Keywords: Sørishavet; Weddellhavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr; zoologi

Autonomous observing platform CO2 data shed new light on the Southern Ocean carbon cycle - Olsen, Are (Global Biogeochemical Cycles, 2017)
While the number of surface ocean CO2 partial pressure (pCO2) measurements has soared the recent decades, the Southern Ocean remains undersampled. Williams et al. (2017, https://doi.org/10.1002/2016GB005541) now present pCO2 estimates based on data from pH-sensor equipped Bio-Argo floats, which have been measuring in the Southern Ocean since 2014. The authors demonstrate the utility of these data for understanding the carbon cycle in this region, which has a large influence on the distribution of CO2 between the ocean and atmosphere. Biogeochemical sensors deployed on autonomous platforms hold the potential to shape our view of the ocean carbon cycle in the coming decades.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; kartlegging; klimaendringer; klimatologi; observasjoner

Application of remotely piloted aircraft systems in observing the atmospheric boundary layer over Antarctic sea ice in winter - Jonassen, Marius O; Tisler, Priit; Altstädter, Barbara; Scholtz, Andreas; Vihma, Timo; Lampert, Astrid; König-Langlo, Gert; Lüpkes, Christof (Polar Research, 2015)
The main aim of this paper is to explore the potential of combining measurements from fixed- and rotary-wing remotely piloted aircraft systems (RPAS) to complement data sets from radio soundings as well as ship and sea-ice-based instrumentation for atmospheric boundary layer (ABL) profiling. This study represents a proof-of-concept of RPAS observations in the Antarctic sea-ice zone. We present first results from the RV Polarstern Antarctic winter expedition in the Weddell Sea in June–August 2013, during which three RPAS were operated to measure temperature, humidity and wind; a fixed-wing small unmanned meteorological observer (SUMO), a fixed-wing meteorological mini-aerial vehicle, and an advanced mission and operation research quadcopter. A total of 86 RPAS flights showed a strongly varying ABL structure ranging from slightly unstable temperature stratification near the surface to conditions with strong surface-based temperature inversions. The RPAS observations supplement the regular upper air soundings and standard meteorological measurements made during the campaign. The SUMO and quadcopter temperature profiles agree very well and, excluding cases with strong temperature inversions, 70% of the variance in the difference between the SUMO and quadcopter temperature profiles can be explained by natural, temporal, temperature fluctuations. Strong temperature inversions cause the largest differences, which are induced by SUMO’s high climb rates and slow sensor response. Under such conditions, the quadcopter, with its slower climb rate and faster sensor, is very useful in obtaining accurate temperature profiles in the lowest 100 m above the sea ice. Keywords: Remotely piloted aircraft systems; unmanned aerial vehicles; Weddell Sea; polar meteorology; Antarctic; boundary layer meteorology.
Keywords: Sørishavet; Weddellhavet; fjernstyrte flysystemer; havis; meteorologi; målinger; observasjoner; sjøis; ubemannede luftfartøyer

Investigating the recent apparent hiatus in surface temperature increases: 2. Comparison of model ensembles to observational estimates - Thorne, Peter; Outten, Stephen; Bethke, Ingo; Seland, Øyvind (Journal of Geophysical Research: Atmospheres, 2015)
To assess published hypotheses surrounding the recent slowdown in surface warming (hiatus), we compare five available global observational surface temperature estimates to two 30-member ensembles from the Norwegian Earth System Model (NorESM). Model ensembles are initialized in 1980 from the transient historical runs and driven with forcings used in the CMIP5 experiments and updated forcings based upon current observational understanding, described in Part 1. The ensembles' surface temperature trends are statistically indistinguishable over 1998–2012 despite differences in the prescribed forcings. There is thus no evidence that forcing errors play a significant role in explaining the hiatus according to NorESM. The observations fall either toward the lower portion of the ensembles or, for some observational estimates and regions, outside. The exception is the Arctic where the observations fall toward the upper ensemble bounds. Observational data set choices can make a large difference to findings of consistency or otherwise. Those NorESM ensemble members that exhibit Nino3.4 Sea Surface Temperature (SST) trends similar to observed also exhibit comparable tropical and to some extent global mean trends, supporting a role for El Nino Southern Oscillation in explaining the hiatus. Several ensemble members capture the marked seasonality observed in Northern Hemisphere midlatitude trends, with cooling in the wintertime and warming in the remaining seasons. Overall, we find that we cannot falsify NorESM as being capable of explaining the observed hiatus behavior. Importantly, this is not equivalent to concluding NorESM could simultaneously capture all important facets of the hiatus. Similar experiments with further, distinct, Earth System Models are required to verify our findings.
Keywords: Antarktis; atmosfæren; fjernmåling; geofysikk; klimaendringer; klimatologi; meteorologi; observasjoner; polarområdene; temperatur

Decrease in stomach contents in the Antarctic minke whale (Balaenoptera bonaerensis) in the Southern Ocean - Konishi, Kenji; Hakamada, Takashi; Kiwada, Hiroshi; Kitakado, Toshihide; Walløe, Lars (Polar Biology, 2014)
Keywords: Sørishavet; hvaler; krill; marin biologi; observasjoner

Observations of cetaceans in the south-east Atlantic sector of the Southern Ocean, during summer 2008 - Nøttestad, Leif; Krafft, Bjørn; Søiland, Henrik; Skaret, Georg (Polar Biology, 2014)
Keywords: Sørishavet; hvaler; marin biologi; observasjoner; oseanografi

The influence of Nunataks on atmospheric boundary layer convection during summer in Dronning Maud Land, Antarctica - Stenmark, Aurora; Hole, Lars Robert; Voss, Paul; Reuder, Joachim; Jonassen, Marius O (Journal of Geophysical Research: Atmospheres, 2014)
The effects of nunataks on temperature profiles and wind patterns are studied using simulations from the Weather Research and Forecasting model. Simulations are compared to hourly observations from an automatic weather station located at the Troll Research Station in Dronning Maud Land. Areas of bare ground have been implemented in the model, and the simulations correspond well with meteorological measurements acquired during the 4 day simulation period. The nunataks are radiatively heated during daytime, and free convection occurs in the overlying atmospheric boundary layer. The inflow below the updraft forces strong horizontal convergence at the surface, whereas weaker divergence appears aloft. In a control run with a completely ice-covered surface, the convection is absent. In situ observations carried out by a remotely controlled balloon and a small model airplane compare well with model temperature profiles, but these are only available over the ice field upwind to the nunatak.
Keywords: Dronning Maud Land; atmosfæren; geofysikk; meteorologi; nunataker; observasjoner

Better late than never? Interannual and seasonal variability in breeding chronology of gentoo penguins at Stranger Point, Antarctica - Juáres, Mariana A; Santos, M Mercedes; Negrete, Javier; Santos, M Rita; Mennucci, Jorge A; Rombolá, Emilce; Longarzo, Lucrecia; Coria, Néstor R; Carlini, Alejandro R (Polar Research, 2013)
Rapid climate change recorded in the western Antarctic Peninsula confronts species with less predictable conditions in the marine and terrestrial environments. We analysed the breeding chronology and nesting site selection of gentoo penguins (Pygoscelis papua) at King George Island (Isla 25 de Mayo), Antarctica, during four seasons in which differences in snow presence and persistence on the ground were observed. We recorded an overall delay as well as seasonal asynchrony at the beginning of reproduction for those years with higher snow deposition. A redistribution of breeding groups was also observed. Nevertheless, the population breeding success and chicks’ weight at fledging remained relatively constant, despite the delay in breeding chronology, the increased duration of foraging trips during the guard stage and the decreased weight of stomach contents during the crèche stage. We suggest that the plasticity of their trophic biology, along with the flexibility of their breeding phenology and relocation of breeding groups, may be complementary reasons why gentoo penguin populations in the region have remained stable in spite of the changing conditions currently registered. Keywords: Antarctica; breeding delay; breeding phenology; snow; Pygoscelis papua; Euphausia superba.
Keywords: Antarktis; klimaendringer; krill; observasjoner; pingviner; plankton; reproduksjon; snø; zoologi

New at-sea records of pelagic seabirds in the South Atlantic Ocean and Antarctica - Orgeira, José Luis; Scioscia, Gabriela; Torres, Mónica Anilía; Dellabianca, Natalia Andrea (Polar Research, 2013)
During ship-based seabird surveys in the south Atlantic and Antarctica in the austral summers of 1994/95, 2009, 2010, 2011 and 2012, we documented at-sea distributions of Buller’s albatross (Thalassarche bulleri), Atlantic petrel (Pterodroma incerta), soft-plumaged petrel (Pterodroma mollis), Kerguelen petrel (Lugensa brevirostris) and great-winged petrel (Pterodroma macroptera). In some cases, sightings were considered as extralimital, but for other species updating their distributions in the literature seems warranted. Atlantic petrel, for example, has been regularly observed in the Drake Passage and north of the Antarctic Peninsula for about 30 years, but the distribution of this species has not been updated in the literature. The observations reported here will contribute to update the at-sea distributions of these species and to changes in their distributions. Keywords: Seabirds; Antarctica; South Atlantic Ocean; distribution.
Keywords: Antarktis; Sørishavet; marin zoologi; observasjoner; ornitologi; petreller; sjøfugler

Observed variations in multidecadal Antarctic sea ice trends during 1979–2012 - Simpkins, Graham R; Ciasto, Laura M; England, Matthew H (Geophysical Research Letters, 2013)
The spatiotemporal sensitivity of Antarctic sea ice season length trends are examined using satellite-derived observations over 1979–2012. While the large-scale spatial structure of multidecadal trends has varied little during the satellite record, the magnitude of trends has undergone substantial weakening over the past decade. This weakening is particularly evident in the Ross and Bellingshausen Seas, where a ∼25–50% reduction is observed when comparing trends calculated over 1979–2012 and 1979–1999. Multidecadal trends in the Bellingshausen Sea are found to be dominated by variability over subdecadal time scales, particularly the rapid decline in season length observed between 1979 and 1989. In fact, virtually no trend is detectable when the first decade is excluded from trend calculations. In contrast, the sea ice expansion in the Ross Sea is less influenced by shorter-term variability, with trends shown to be more consistent at decadal time scales and beyond. Understanding these contrasting characteristics have implications for sea ice trend attribution.
Keywords: Sørishavet; havis; klimatologi; observasjoner; satellite bilder; sjøis

Direct observations of nitric oxide produced by energetic electron precipitation into the Antarctic middle atmosphere - Newnham, David A; Espy, Patrick J; Clilverd, Mark A; Rodger, Craig J; Seppälä, Annika; Maxfield, David J; Hartogh, Paul; Holmén, Kim; Horne, Richard B (Geophysical Research Letters, 2011)
We report the first ground-based passive microwave observations made from Troll station, Antarctica, which show enhanced mesospheric nitric oxide (NO) volume mixing ratio reaching levels of 1.2 ppmv, or 2–3 orders of magnitude above background, at 70–80 km during small, relatively isolated geomagnetic storms in 2008. The mesospheric NO peaked 2 days after enhanced NO at higher altitudes (110–150 km) measured by the SABER satellite, and 2 days after peaks in the >30 keV and >300 keV electron flux measured by POES, although the 300 keV electron flux remained high. High time resolution data shows that mesospheric NO was enhanced at night and decayed during the day and built up to high levels over a period of 3–4 days. The altitude profile of mesospheric NO suggests direct production by ∼300 keV electron precipitation. Simulations using the Sodankylä Ion and Neutral Chemistry model show that the delay between thermospheric and mesospheric NO enhancements was primarily a result of the weaker production rate at lower altitudes by ∼300 keV electrons competing against strong day-time losses.
Keywords: Dronning Maud Land; Troll forskningsstasjon; geofysikk; geomagnetiske stormer; meteorologi; observasjoner; radiometer

An inter-comparison of six latent and sensible heat flux products over the Southern Ocean - Yu, Lejiang; Zhang, Zhanhai; Zhong, Shiyuan; Zhou, Mingyu; Gao, Zhiqiu; Wu, Huiding; Sun, Bo (Polar Research, 2011)
The latent heat fluxes (LHF) and sensible heat fluxes (SHF) over the Southern Ocean from six different data sets are inter-compared for the period 1988- 2000. The six data sets include three satellite-based products, namely, the second version of the Goddard Satellite-Based Surface Turbulent Fluxes data set (GSSTF-2), the third version of the Hamburg Ocean Atmosphere Parameters and Fluxes from Satellite Data (HOAPS-3) and the Japanese Ocean Fluxes Data Sets with Use of Remote Sensing Observations (J-OFURO); two global reanalysis products, namely, the National Centers for Environmental Prediction-Department of Energy Reanalysis 2 data set (NCEP-2) and the European Centre for Medium-Range Weather Forecasts 40 Year Re-analysis data set (ERA-40); and the Objectively Analyzed Air-Sea Fluxes for the Global Oceans data set (OAFlux). All these products reveal a similar pattern in the averaged flux fields. The zonal mean LHF fields all exhibit a continuous increase equatorward. With an exception of HOAPS-3, the zonal mean SHF fields display a minimum value near 50°S, increasing both pole- and equatorward. The differences in the standard deviation for LHF are larger among the six data products than the differences for SHF. Over the regions where the surface fluxes are significantly influenced by the Antarctic Oscillation and the Pacific-South American teleconnection, the values and distributions of both LHF and SHF are consistent among the six products. It was found that the spatial patterns of the standard deviations and trends of LHF and SHF can be explained primarily by sea-air specific humidity and temperature differences; wind speed plays a minor role. Keywords: Latent heat flux; sensible heat flux; Southern Ocean.
Keywords: Sørishavet; klimatologi; meteorologi; observasjoner

Evaluating CERES angular distribution models for snow using surface reflectance observations from the East Antarctic Plateau - Hudson, Stephen R; Kato, Seiji; Warren, Stephen G (Journal of Geophysical Research: Atmospheres, 2010)
Clouds and the Earth's radiant energy system (CERES) is a satellite-based remote sensing system designed to monitor the Earth's radiation budget. In this paper we examine uncertainties in the angular distribution models (ADMs) used by CERES over permanently snow covered surfaces with clear skies. These ADMs are a key part of the CERES data processing algorithms, used to convert the observed upwelling radiance to an estimate of the upwelling hemispheric flux. We model top-of-atmosphere anisotropic reflectance factors using an atmospheric radiative transfer model with a lower boundary condition based on extensive reflectance observations made at Dome C, Antarctica. The model results and subsequent analysis show that the CERES operational clear-sky permanent-snow ADMs are appropriate for use over Dome C, with differences of less than 5% between the model results and the ADMs at most geometries used by CERES operationally. We show that the uncertainty introduced into the flux estimates through the use of the modeled radiances used in the ADM development is small when the fluxes are averaged over time and space. Finally, we show that variations in the angular distribution of radiance at the top of the atmosphere due to atmospheric variability over permanently snow covered regions are in most cases unlikely to mask the real variations in flux caused by these atmospheric variations.
Keywords: Antarktis; atmosfæren; fjernmåling; klima; meteorologi; observasjoner; snø; solstråling

A comparison of shortwave reflectance over the East Antarctic Plateau observed by CERES to that estimated from surface reflectance observations - Hudson, Stephen R; Warren, Stephen G; Kato, Seiji (Journal of Geophysical Research: Atmospheres, 2010)
Spectral albedo and bidirectional reflectance of snow were measured at Dome C on the East Antarctic Plateau for wavelengths of 350–2400 nm and solar zenith angles of 52°–87°. A parameterization of bidirectional reflectance, based on those measurements, is used as the lower boundary condition in the atmospheric radiation model SBDART to calculate radiance and flux at the top of the atmosphere (TOA). The model's atmospheric profile is based on radiosoundings at Dome C and ozonesoundings at the South Pole. Computed TOA radiances are integrated over wavelength for comparison with the Clouds and the Earth's Radiant Energy System (CERES) shortwave channel. CERES radiance observations and flux estimates from four clear days in January 2004 and January 2005 from within 200 km of Dome C are compared with the TOA radiances and fluxes computed for the same solar zenith angle and viewing geometry, providing 11,000 comparisons. The measured radiance and flux are lower than the computed values. The median difference is about 7% for CERES on Terra, and 9% on Aqua. Sources of uncertainty in the model and observations are examined in detail and suggest that the measured values should be less than the computed values, but only by 1.7% ± 4%. The source of the discrepancy of about 6% cannot be identified here; however, the modeled values do agree with observations from another satellite instrument (Multiangle Imaging Spectroradiometer), suggesting that the CERES calibration must be considered a possible source of the discrepancy.
Keywords: Antarktis; atmosfæren; fjernmåling; meteorologi; observasjoner; solstråling

Antarctic clouds - Lachlan-Cope, Tom (Polar Research, 2010)
Sensitivity studies with global climate models show that, by their influence on the radiation balance, Antarctic clouds play a major role in the climate system, both directly at high southern latitudes and indirectly globally, as the local circulation changes lead to global teleconnections. Unfortunately, observations of cloud distribution in the Antarctic are limited and often of low quality because of the practical difficulty in observing clouds in the harsh Antarctic environment. The best surface observations suggest that the fractional cloud cover at the South Pole is around 50–60% in all seasons, whereas the cloud cover rises to around 80–90% close to the coast of the continent. Microphysical observations of cloud parameters are also very sparse in the Antarctic. However, the few measurements that do exist show predominantly ice-crystal clouds across the interior, with mixed-phase clouds close to the coasts. Crystal sizes vary from 5 to 30 mm (effective radius) in the interior to somewhat larger ice crystals and water drops near the coast. A wide range of crystal shapes is observed at all sites. This review considers the available cloud observations and highlights the importance of Antarctic clouds and the need for better observations in the future.
Keywords: Antarktis; klimatologi; meteorologi; observasjoner; satellitt bilder; skyer

Movements and dive behaviour of two leopard seals (Hydrurga leptonyx) off Queen Maud Land, Antarctica - Nordøy, Erling S; Blix, Arnoldus Schytte (Polar Biology, 2009)
Keywords: Sørishavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr

Decadal decrease of Antarctic sea ice extent inferred from whaling records revisited on the basis of historical and modern sea ice records - Ackley, Stephen; Wadhams, Peter; Comiso, Josefino C; Worby, Anthony P (Polar Research, 2003)
In previous work, whaling catch positions were used as a proxy record for the position of the Antarctic sea ice edge and mean sea ice extent greater than the present one spanning 2.8° latitude was postulated to have occurred in the pre-1950s period, compared to extents observed since 1973 from microwave satellite imagery. The previous conclusion of an extended northern latitude for ice extent in the earlier epoch applied only to the January (mid-summer) period. For this summer period, however, there are also possible differences between ship and satellite-derived measurements. Our work showed a consistent summer offset (November– December), with the ship-observed ice edge 1 - 1.5° north of the satellitederived ice edge. We further reexamine the use of whale catch as an ice edge proxy where agreement was claimed between the satellite ice edge (1973–1987) and the ship whale catch positions. This examination shows that, while there may be a linear correlation between ice edge position and whale catch data, the slope of the line deviates from unity and the ice edge is also further north in the whale catch data than in the satellite data for most latitudes. We compare the historical (direct) record and modern satellite maps of ice edge position accounting for these differences in ship and satellite observations. This comparison shows that only regional perturbations took place earlier, without significant deviations in the mean ice extents, from the pre-1950s to the post-1970s. This conclusion contradicts that previously stated from the analysis of whale catch data that indicated Antarctic sea ice extent changes were circumpolar rather than regional in nature between the two periods.
Keywords: Sørishavet; Weddellhavet; endringer; havis; historisk; hvalfangere; hvalfangst; iskant; observasjoner; satellite bilder; sjøis

A hindcast simulation of Arctic and Antarctic sea ice variability, 1955-2001 - Fichefet, Thierry; Goosse, Hugues; Morales Maqueda, Miguel Angel (Polar Research, 2003)
A hindcast simulation of the Arctic and Antarctic sea ice variability during 1955–2001 has been performed with a global, coarse resolution ice–ocean model driven by the National Centers for Environmental Prediction / National Center for Atmospheric Research reanalysis daily surface air temperatures and winds. Both the mean state and variability of the ice packs over the satellite observing period are reasonably well reproduced by the model. Over the 47-year period, the simulated ice area (defined as the total ice-covered oceanic area) in each hemisphere experiences large decadal variability together with a decreasing trend of ~1 % per decade. In the Southern Hemisphere, this trend is mostly caused by an abrupt retreat of the ice cover during the second half of the 1970s and the beginning of the 1980s. The modelled ice volume also exhibits pronounced decadal variability, especially in the Northern Hemisphere. Besides these fluctuations, we detected a downward trend in Arctic ice volume of 1.8 % per decade and an upward trend in Antarctic ice volume of 1.5 % per decade. However, caution must be exercised when interpreting these trends because of the shortness of the simulation and the strong decadal variations. Furthermore, sensitivity experiments have revealed that the trend in Antarctic ice volume is model-dependent.
Keywords: Sørishavet; forskning; geofysikk; havis; observasjoner; polarområdene; satellitt; sjøis

Arctic and Antarctic ozone layer observations: chemical and dynamical aspects of variability and long-term changes in the polar stratosphere - Rex, Markus; Dethloff, Klaus; Handorf, Dörthe; Herber, Andreas; Lehmann, Ralph; Neuber, Roland; Notholt, Justus; Rinke, Annette; von der Gathen, Peter; Weisheimer, Antje; Gernandt, Hartwig (Polar Research, 2000)
The altitude dependent variability of ozone in the polar stratosphere is regularly observed by balloon-borne ozonesonde observations at Neumayer Station (70°S) in the Antarctic and at Koldewey Station (79°N) in the Arctic. The reasons for observed seasonal and interannual variability and long-term changes are discussed. Differences between the hemispheres are identified and discussed in light of differing dynamical and chemical conditions. Since the mid- 1980s, rapid chemical ozone loss has been recorded in the lower Antarctic stratosphere during the spring season. Using coordinated ozone soundings in some Arctic winters, similar chemical ozone loss rates have been detected related to periods of low temperatures. The currently observed cooling trend of the stratosphere, potentially caused by the increase of anthropogenic greenhouse gases, may further strengthen chemical ozone removal in the Arctic. However, the role of internal climate oscillations in observed temperature trends is still uncertain. First results of a 10000 year integration of a low order climate model indicate significant internal climate variability. on decadal time scales, that may alter the effect of increasing levels of greenhouse gases in the polar stratosphere.
Keywords: Antarktis; drivhusgasser; klimaendringer; klimagasser; meteorologi; observasjoner; ozonlaget; polarområdene; stratosfæren

Sub-surface melting in blue-ice fields in Dronning Maud Land, Antarctica: observations and modelling - Bøggild, Carl Egede; Winther, Jan-Gunnar; Sand, Knut; Elvehøy, Hallgeir (Annals of Glaciology, 1995)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; NARE 1993/94; glasiologi; observasjoner

Hydrographic observations from the Weddell Sea during the Norwegian Antarctic Research Expedition 1976/77 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; hydrografi; kontinentalsokkel; observasjoner

Flow Around Icebergs - Foldvik, Arne; Gammelsrød, Tor; Gjessing, Yngvar (Annals of Glaciology, 1980)
Publisher: Cambridge University Press
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; glasiologi; isberg; observasjoner; oseanografi; sjøvann

Verdens kaldeste sjøvann - Foldvik, Arne; Gade, Herman G (Naturen, 1978)
Publisher: Universitetsforlaget Place: Oslo
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; observasjoner; oseanografi; sjøvann; vannmasser

Changes in body-weight of men in the Antarctic - Wilson, Ove (British Journal of Nutrition, 1960)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fysiologi; observasjoner

Verdien av de meteorologiske observasjoner fra hvalkokeriene = The value of meteorological observations from whaling factory ships - Vowinckel, E (Norsk hvalfangst-tidende, 1954)
Keywords: Sørishavet; klima; meteorologi; observasjoner

Physiological changes in blood in the Antarctic. A preliminary report - Wilson, Ove (British Medical Journal, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; forskning; fysiologi; medisin; observasjoner